Goal Frustration in Academic Achievement Settings Theories and Applications - Zhou, Mingming (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book provides in-depth description, explanation, and discussion of goal frustration. It brings together a repertoire of perspectives and strategies that educators and scholars from diverse educational contexts have conceptualized and/or implemented in order to monitor, control, or overcome the occurrence of frustration. This book describes the new technologies can be applied in the conceptualization and operationalization of goal frustration. It also discusses the strategies and pedagogies we can use to cope with this emotion. This book offers evidence-based reports of goal frustration as well as data-driven approaches by presenting both theoretical account and empirical evidence that are grounded in educational and psychological research. This work will appeal to a wider readership from practitioners, parents, to educational researchers.
Chapter 1 Nature of goal frustration -- Chapter 2 Operationalization of goal frustration -- Chapter 3 Correlates to goal frustration -- 4 Cross-cultural perspectives on goal frustration -- Chapter 5 Empirical Evidence of Goal Frustration in Asian Academic Settings -- Chapter 6 Ways to monitor and control goal frustration -- Chapter 7 Frustration or Fulfilment? Transform Frustration into Empowerment -- Chapter 8 Concluding remarks.
Keywords: Learning, Psychology of; Education; Learning Theory; Learning Psychology; Education Science